Do front-of-pack 'green labels' increase sustainable food choice and willingness-to-pay in U.K. consumers?. (15th October 2022) - Duckworth, Jay J.; Randle, Mark; McGale, Lauren S.; Jones, Andrew; Doherty, Bob; Halford, Jason C.G.; Christiansen, Paul
Abstract: Aim: In a series of pre-registered online studies, we aimed to elucidate the magnitude of the effect of general sustainability labels on U.K. consumers' food choices. Methods: Four labels were displayed: 'Sustainably sourced', 'Locally sourced', 'Environmentally friendly', and 'Low greenhouse gas emissions' . To ensure reliable results, contingency valuation elicitation was used alongside a novel analytical approach to provide a triangulation of evidence: Multilevel-modelling compared each label vs. no-label; Poisson-modelling compared label vs. label. Socioeconomic status, environmental awareness, health motivations, and nationalism/patriotism were included in our predictive models. Results: Exp.1 Multilevel-modelling ( N  = 140) showed labelled products were chosen 344% more than non-labelled and consumers were willing-to-pay ∼£0.11 more, although no difference between label types was found. Poisson-modelling ( N  = 735) showed consumers chose Sustainably sourced and Locally sourced labels ∼20% more often but were willing-to-pay ∼£0.03 more only for Locally sourced products. Exp.2 was a direct replication. Multilevel-modelling ( N  = 149) showed virtually identical results (labels chosen 344% more, willingness-to-pay ∼£0.10 more), as did Poisson-modelling ( N  = 931) with Sustainably sourced and Locally sourced chosen ∼20% more and willingness-to-pay ∼£0.04 more for Locally sourced products. Environmental concern (specifically the 'propensity to act') was the only consistent predictor of preference for labelled vs. non-labelled products. Conclusions: Findings suggest front-of-pack 'green labels' may yield substantive increases in consumer choice alongside relatively modest increases in willingness-to-pay for environmentally-sustainable foods. Specifically, references to 'sustainable' or 'local' sourcing may have the largest impact. Highlights: Contingency valuation elicitation was used to test four novel sustainability labels. Multilevel and Poisson models offer novel analyses in assessing green label effects. Labelled products were chosen >300% more often than non-labelled products. Consumers were willing to pay ∼£0.10 more for labelled products. The labels Sustainably sourced and Locally sourced were most influential.